Utilizing TPACK Framework in English Language Instruction for High School Students - Wilda Toding, Rufina; Halim, Abd; Abduh, Amirullah; Mahmud, Murni; Halim, Nur Mutmainna; Julianti, Rahmah (JEELS (Journal of English Education and Linguistics Studies), 2024)
This century's learning advancement relies on different information technology mediums. Thus, educators must improve their ICT skills to improve learning and academic performance. There are two main goals of this study: 1) to find out how TPACK is used to teach and learn English in high school; and 2) to find out what problems English teachers run into when they try to use TPACK. The type of study being done is qualitative. Interviews, documentation, and observation were some of the methods used to gather information for this study. This study looks at 34 kids from XII IPA and one English teacher. English teachers' TPACK knowledge comes from how well technology fits with their teaching methods and English subject knowledge. Technology lets the teacher apply several instructional strategies for several learning environments. According to the Merdeka Curriculum, technology allows SMA 13 Makassar students to learn at their own pace and according to their choices. The English teacher utilized Quizizz or Google Classroom to handle assignments and provide timely feedback. Network service variability affects student engagement and learning equity. SMA 13 Makassar students may need help with coursework, internet forums, and extracurricular resources. While TPACK-based teaching depends on online resources, unreliable network connectivity limits availability. English teachers needing digital libraries, web-based platforms, or multimedia materials need consistent internet access. Unreliable access to these tools can interfere with courses requiring live quizzes, direct assessments, or online group projects to help students grasp complex English literature.